Respuesta :
Answer:
x = ± i & ± i√2
Step-by-step explanation:
The given equation is x⁴ + 3x² + 2 = 0
let u = x²
∴ u² + 3u + 2 = 0
∴ ( u + 2 ) ( u + 1 ) = 0
∴ u = -1 or -2
∴ x² = -1 or x² = -2
∴ x = ±√(-1) = ± i
And x = ±√(-2) = ± i √2
Note i = √(-1)
Answer:
[tex]x=\pm\sqrt{2}i\text{ (or) }x=\pm i[/tex]
Step-by-step explanation:
We have been given an equation [tex]x^4 + 3x^2 + 2 = 0[/tex]. We are asked to find the solutions of our given equation using u-substitution.
We can rewrite our given equation as:
[tex](x^2)^2+3x^2+2 = 0[/tex]
Let us assume that [tex]u=x^2[/tex].
[tex]u^2+3u+2 = 0[/tex]
[tex]u^2+2u+u+2 = 0[/tex]
[tex]u(u+2)+1(u+2) = 0[/tex]
[tex](u+2)(u+1) = 0[/tex]
[tex](u+2)=0\text{ (or) }(u+1) = 0[/tex]
[tex]u=-2\text{ (or) }u=-1[/tex]
Upon substituting back the value of u, we will get:
[tex]x^2=-2\text{ (or) }x^2=-1[/tex]
[tex]x=\pm\sqrt{-2}\text{ (or) }x=\pm\sqrt{-1}[/tex]
[tex]x=\pm\sqrt{-1\cdot 2}\text{ (or) }x=\pm\sqrt{-1}[/tex]
Now we will use imaginary unit i. We know that [tex]i^2=-1[/tex].
[tex]x=\pm\sqrt{i^2\cdot 2}\text{ (or) }x=\pm\sqrt{i^2}[/tex]
[tex]x=\pm\sqrt{2}i\text{ (or) }x=\pm i[/tex]
Therefore, the solutions for our given equation are [tex]x=\pm\sqrt{2}i\text{ (or) }x=\pm i[/tex].